The one health problem of azole resistance in Aspergillus fumigatus: current insights and future research agenda. Issue 4 (December 2020) - Verweij, Paul E.; Lucas, John A.; Arendrup, Maiken C.; Bowyer, Paul; Brinkmann, Arjen J.F.; Denning, David W.; Dyer, Paul S.; Fisher, Matthew C.; Geenen, Petra L.; Gisi, Ulrich; Hermann, Dietrich; Hoogendijk, Andre; et al.
Abstract: Azole resistance is a concern for the management of diseases caused by Aspergillus fumigatus in humans. Azole fungicide use in the environment has been identified as a possible cause for development of resistance, which increases the complexity and number of stakeholders involved in this emerging problem. A workshop was held in Amsterdam early 2019 in which stakeholders, including medical and agricultural researchers, representatives from the government, public health, fungicide producers and end-users, reviewed the current evidence supporting environmental selection for resistance and to discuss which research and measures are needed to retain the effectiveness of the azole class for environmental and medical applications. This paper provides an overview of the latest insights and understanding of azole resistance development in the clinical setting and the wider environment. A One Health problem approach was undertaken to list and prioritize which research will be needed to provide missing evidence and to enable preventive interventions. Highlights: Environmental azole resistance selection in A . fumigatus threatens medical therapy. Certain azole fungicide applications have a low risk of resistance selection. Hotspots involve A. fumigatus growth in plant waste containing azole residues. Environmental resistance burden may be reduced through a One-Health approach. AMR research and action plans should include fungal resistance.